PHOTOGRAPHY – Pariah of Art or Outpost of Creativity? - WILL, RALF G (IJRDO - Journal of Social Science and Humanities Research, 2019)
In my 5-pointer Theory of Art, personality plays an integral part. Could also be called historical background of artist, or the humanising of ignorance, rejection and cold-shoulderd aloofness. Personality forms a range of experiences that build character, showcasing individual identity and creative choice. And viewed over a longer period of time, the artist`s overall message can also be termed personality. Even stand for a specific streak of creative life that may not have looked as such when it first started out or when it passed the half-way mark, huffing, puffing, struggling along, catching its breath from plenty strain and stress, yet that comes out a winner at the end of the rat race! Not a winner as in win or lose but becomes an artist and achieves fulfillment in a life well spent and dedicated to unravelling value and exposing insincerity.